Applications of Molecularly Imprinted Films - Sarbu, Andrei (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
Molecularly imprinted polymers are materials that have voids that are complementary in shape, size, and electronic environment to a specific molecule used for preparation, known as the template. These voids are specific recognition sites that bind the templates preferentially and are used specifically for biomimetic sensors and for solid-phase extraction. Because the specific surface is very important during this process, the use of films and membranes is preferred. This book contains four articles dedicated to sensor application (three research articles and one review) and one research article dedicated to solid-phase extraction.